2021
DOI: 10.3389/fcvm.2021.705487
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Myocardial Strain and Late Gadolinium Enhancement by Cardiac Magnetic Resonance After a First Anterior ST-Segment Elevation Myocardial Infarction

Abstract: Objectives: To investigate the correlation of cardiac magnetic resonance (CMR) feature-tracking with conventional CMR parameters in patients with a first anterior ST-segment elevation myocardial infarction (STEMI).Methods: This sub-analysis of OCTAMI (Optical Coherence Tomography Examination in Acute Myocardial Infarction) registry included 129 patients who finished a CMR examination 1 month after a first anterior STEMI. Cine images were applied to calculate both global and segmental left ventricular peak stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
1
26
2
Order By: Relevance
“…Consequently, in our analysis LGE might represent not only scar, but also edema, as scans were obtained within a short period of time after the event. Similarly, Yu et al ( 15 ) found in a patient cohort scanned within 1 month after the infarction a SCS cut-off of –10.2%, assessed by CMR-FT that yielded LGE detection with a sensitivity of 80% and specificity of 85%. When comparing different techniques (i.e., CMR-FT and TT) in patients after STEMI, TT showed a higher interobserver variability and correlated less strongly with infarct and showed overall higher values for circumferential strain ( 21 , 22 ), a possible factor contributing to different cut-off values and differences in the diagnostic performances.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Consequently, in our analysis LGE might represent not only scar, but also edema, as scans were obtained within a short period of time after the event. Similarly, Yu et al ( 15 ) found in a patient cohort scanned within 1 month after the infarction a SCS cut-off of –10.2%, assessed by CMR-FT that yielded LGE detection with a sensitivity of 80% and specificity of 85%. When comparing different techniques (i.e., CMR-FT and TT) in patients after STEMI, TT showed a higher interobserver variability and correlated less strongly with infarct and showed overall higher values for circumferential strain ( 21 , 22 ), a possible factor contributing to different cut-off values and differences in the diagnostic performances.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have reported a correlation of strain with the presence of LGE in STEMI patients (15,16) and MVO in addition to LGE seems to have a greater effect on strain (i.e., global) compared to LGE alone (17,18). Furthermore, it has been demonstrated that segmental strain bears the potential to detect MVO with high accuracy, however, specific cut-off values vary between groups due to different patient cohorts and the use of different modalities (i.e., echocardiographic strain or tagging sequences).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…CMR-FT is a more feasible approach based on the fast postprocessing of cine images, acquiring strain information (e.g., strain, strain rate, rotational mechanics) globally or segmentally in three orthogonal directions: longitudinal, circumferential and radial ( 50 ). Multiple strain parameters have been demonstrated their association with CMR tagging ( 128 ), LGE ( 129 ) and histological examination ( 130 ).…”
Section: Detection: Laboratory Biomarkers and Imaging Techniquesmentioning
confidence: 99%
“…Not surprisingly, the relationship between segmental strain at followup and baseline-LGE declined by trend at six months. This development is also in uenced by the reduction of LGE extent over time, with LGE overestimating scar in the acute phase of MI 18,19,25 . Hence, strain at follow-up could re ect the improvement of myocardial function in former LGE + segments.…”
mentioning
confidence: 99%